2007
DOI: 10.1080/08905430701536565
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni: A Review of its Characteristics, Pathogenicity, Ecology, Distribution, Subspecies Characterization and Molecular Methods of Detection

Abstract: Campylobacter jejuni is considered to be the leading cause of enteric illness in the United States and other industrialized nations, causing mild to severe symptoms including serious infections of the extremities and permanent neurological symptoms. The organism is a cytochrome oxidase positive, microaerophilic, curved Gram-negative rod exhibiting corkscrew motility and is carried in the intestine of many wild and domestic animals, particularly avian species including poultry, where the intestine is colonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 257 publications
1
38
0
8
Order By: Relevance
“…(Hörman, 2004). This is consistent with the fact that the majority of Campylobacteraceae are not able to multiply outside of animal hosts and survive poorly in the environment due to light and temperature sensitivity (Levin, 2007).…”
Section: Watersupporting
confidence: 73%
See 1 more Smart Citation
“…(Hörman, 2004). This is consistent with the fact that the majority of Campylobacteraceae are not able to multiply outside of animal hosts and survive poorly in the environment due to light and temperature sensitivity (Levin, 2007).…”
Section: Watersupporting
confidence: 73%
“…(Snelling, 2005) It is suggested that since thermophilic Campylobacter species grow best between 37°C and 42°C, but not below 30°C that they be called thermotolerant (Levin, 2007). This is significant insofar as it relates to survival rates of Campylobacter on food contact surfaces.…”
Section: Growth and Survival Characteristicsmentioning
confidence: 99%
“…It is frequently isolated from the gastrointestinal tract of birds, humans and other mammals (Stintzi 2003;Alter and Scherer 2006;Murphy et al 2006). Symptoms of C. jejuni infection in humans can be mild (including diarrhoea) and occasionally severe, leading to meningitis, pneumonia, miscarriage, and Guillain-Barré syndrome (Levin 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the Republic of Croatia, campylobacteriosis has been a notifiable disease since 2007, with 1642 cases reported in 2014, ranking it the leading zoonosis in the country (3). Campylobacter is a genus of ubiquitous bacteria that have been isolated from a great variety of sources including water, soil, insects, domestic and wild mammals, domestic poultry, and wild birds (4). Meat from intensive poultry production, primarily broilers, is the main source of campylobacteriosis in humans.…”
Section: Introductionmentioning
confidence: 99%